자궁경부암의 전골반방사선치료 후 발생한 대퇴골두 무혈성괴사 2예 - 유정일(Jeongil Yu), 허승재(Seung Jae Huh), 박원(Won Park), 오동렬(Dongryul Oh), 이정애(Jung Ae Lee) (Radiation oncology journal, 2008)
대퇴골두 무혈성괴사는 혈류장애로 인해 대퇴골두의 골세포 괴사가 나타나는 것으로 여러 원인 중 방사선치료도 하나의 원인으로 알려져 있으나 발병률에 대해서는 보고된 바 없는 상태이다. 저자들은 삼성서울병원에서 전골반 방사선치료를 받은 자궁암환자 577명 중 2명의 환자에서 대퇴골두 무혈성괴사를 경험하였다. 2예 모두 전형적인 방사선학적 소견을 보였다. 골반 방사선치료 후 발생하는 대퇴골두 무혈성괴사는 매우 드물게 나타나지만 방사선 조사 범위에 국한된 특징적인 영상의학적 소견을 보이므로 진단에 유념해야 하겠다. Avascular necrosis (AVN) is a disease characterized by the temporary or permanent loss of the blood supply to the bones, resulting from many possible causes, including radiation therapy. The femoral head is known to be the most common site of AVN. The authors encountered two cases of AVN of the femoral head among 557 patients with cervical cancer treated with whole pelvic radiation therapy at the Samsung Medical Center. AVN of the femoral head was presented with a sclerotic density change in a plain roentgenography and a decreased signal intensity lesion on the T1 and T2 weighted phases of a magnetic resonance image (MRI). Although it is a very rare complication after whole pelvic radiation therapy, AVN of the femoral head should be considered when characteristic imaging findings appear on follow-up examinations. KCI Citation Count: 1